Structural dichotomy of the mind; the role of sexual neuromodulators - Ion G. Motofei; David L. Rowland (Journal of Mind and Medical Sciences)
The mind (mental function) and sexuality represent two distinct environmental functions, but which are supported within the brain by a common (somatic-autonomic) neurobiological substrate. As a consequence, mental function takes on autonomic characteristics from the sexual-autonomic system (like autonomy, duality), while sexual function takes on features from mental functioning (such as lateralization). In this paper we discuss the lateralized action of two classes of sexual neuromodulators: hormones and pheromones. This process of lateralization is assimilated with the structural dichotomy of the mind. A relatively similar process but related to informational dichotomy of the mind will be presented in a forthcoming paper. Structural and informational dichotomies of the mind represent essential aspects that need clarification in order to continue the solving of the mind-body process, a work in progress articulated through a succession of papers.